Predictors of Progression in Intraplaque Hemorrhage Volume in Patients With Carotid Atherosclerosis: A Serial Magnetic Resonance Imaging Study - Mingming, Lu; Peng, Peng; Lichen, Zhang; Shaohua, Liu; Fei, Yuan; Hongtao, Zhang; Shitong, Liu; Yao, He; Xihai, Zhao; Jianming, Cai (Frontiers in Neurology, 2022)
Background and Purpose This study aimed to investigate the arterial disease risk factors for the progression of intraplaque hemorrhage (IPH) in patients with carotid atherosclerosis using serial high-resolution magnetic resonance (MR) imaging. Methods Consecutive symptomatic patients who had MRI evidence of intraplaque hemorrhage present in the ipsilateral carotid artery with respect to the side of the brain affected by stroke or TIA were recruited in the study. All the patients underwent follow-up MR imaging at least 6 months after baseline. The annual change in IPH and other carotid plaque morphology was calculated, and a tertile method was used to classify the plaques as progressed or not with respect to IPH volume using the software CASCADE. Logistic regression and receiver operating characteristic (ROC) curve were conducted to evaluate the risk factors for the progression of IPH. Results A total of thirty-four symptomatic patients (mean age: 67.1 years, standard deviation [SD]: 9.8 years, 27 men) were eligible for the final analysis, and contralateral plaques containing IPH were seen in 11 of these patients (making 45 plaques with IPH in total). During mean 16.6-month (SD: 11.0 months) follow-up, the overall annual change in IPH volume in 45 plaques with IPH was mean −10.9 mm3 (SD: 49.1 mm3). Carotid plaques were significantly more likely to be classified in progressed IPH group if the patient was taking antiplatelet agent at baseline (OR: 9.76; 95%CI: 1.05 to 90.56; p = 0.045), had a baseline history of current or past smoking (OR: 9.28; 95%CI: 1.26 to 68.31; p = 0.029), or had a larger baseline carotid plaque-containing vessel wall volume (OR: 1.36 per 10 mm3; 95%CI: 1.02 to 1.81; p = 0.032) after adjustments for confounding factors. ROC analysis indicated that the combination of these three risk factors in the final model produced good discriminatory value for the progressed IPH group (area under the curve: 0.887). Conclusions Taking an antiplatelet agent at baseline, a baseline history of current or past smoking and larger baseline carotid plaque-containing vessel wall volume were independently predictive of plaques being in the progressed IPH group. Our findings indicate that awareness and management of such risk factors may reduce the risk of intraplaque hemorrhage progression.